The role of verbal eliciting stimuli on the development of sensibility to others in psychotherapy - Gomes, Renata Cristina; de Rose, Julio C. (Perspectivas em Análise do Comportamento, 2024)
The importance that individuals are capable of responding to future consequences and the consequences of their behavior is recognized either by professionals and researchers in the field of Psychology and culturally. Behavioral psychotherapists are usually concerned about developing their client’s sensibility to others. However, many interventions on that subject are effective in developing the client’s ability to describe what would be happening to others, but not necessarily promoting an improvement in the probability of actually helping other people outside therapy session. The analysis of those interventions from a RFT perspective allows the supposition that, when the psychotherapist is able to establish equivalence relations between events descriptions which elicit emotional responding and the events occurring with another person, psychotherapy clients are more willing to help. The aim of this study is to present a conceptual proposal, grounded in a literature review with empirical basis for a research program on psychotherapeutic interventions that target the development of sensitivity to others and the corresponding issuance of helping actions.